Research progress of single cell RNA sequencing in nervous system - Lei Hu; Lixin Qi; Zhenlang Lin; Jianghu Zhu; Min Zhang (Molecular Biology Reports, 2026)

Dl‑3‑n‑Butylphthalide Protects the Blood–Brain Barrier in Neonatal Hypoxic‑Ischemic Brain Damage by Alleviating Endothelial Cell Ferroptosis via the SLC7A11/GSH/GPX4 Pathway - Jiahao Ou; Qianqian Yu; Yuqi Luo; Ming Shen; Jia Lou; Saizhi Jiang; BangMing ye; LiZi Lin; Jianghu Zhu; Zhenlang Lin; Mingchu Fang (Molecular Neurobiology, 2026)

Therapeutic Mechanisms of Stem Cell–Derived Exosomes for Neurological Disorders: An Overview - Congying Lin; Lixin Qi; Xiuying Gao; Lei Hu; Bo Qian; Yixuan Deng; Chunting Zhou; Chenyi Wang; Guanhao Liu; Qiang Ding; Zhenlang Lin; Xuwei Zhu; et al. (Molecular Neurobiology, 2026)

Parthenolide Exerts Protection against Hypoxic-Ischemic Brain Damage in Neonatal Rats by Inhibiting Perk-Mediated Endoplasmic Reticulum Stress - Niping Mao; Yihui Zheng; Junhui Yuan; Xiaoli Feng; Yi Ren; Xun Wang; Xiaoyue Tao; Xingyun Wang; Mingchu Fang; Zhenlang Lin (Molecular Neurobiology, 2026)

Inhibition of Neuroinflammation by Costunolide Attenuates Hypoxic-Ischemic Brain Damage via the PI3K/AKT Pathway in Neonatal Rats - Yingying Hu; Rengcheng Qian; Yifeng He; Qiqi Gao; Xun Wang; Huilin Lin; Wei Lin; Yu Fang; Jianghu Zhu; Xingyun Wang; Yan Nan; Zhenlang Lin (Molecular Neurobiology, 2026)

Application of nanomaterials in central nervous system disorders - Yixuan Deng; Yani Feng; Bangming Ye; Lei Hu; Lixin Qi; Chenyi Wang; Chunting Zhou; Guanhao Liu; Xiuying Gao; Congying Lin; Qiang Ding; Ziming Zhao; et al. (Psychopharmacology, 2025)

Glutathione-protected Au22 Nanoclusters Ameliorates Hypoxic-Ischemic Brain Damage in Neonatal Rats via Sirt3/SOD2 Signaling Pathway - Yihui Zheng; Xiaoli Feng; Xinying Hu; Tingyu Zhu; Jialuo Ding; Niping Mao; Hejie Xu; Jia Lou; Junhui Yuan; Xingyun Wang; Zhenlang Lin; Zhenkun Lin; et al. (Molecular Neurobiology, 2025)

FGF21 Alleviates Hypoxic-Ischemic White Matter Injury in Neonatal Mice by Mediating Inflammation and Oxidative Stress Through PPAR-γ Signaling Pathway - Mingchu Fang; Liying Lu; Jia Lou; Jiahao Ou; Qianqian Yu; Xiaoyue Tao; Jianghu Zhu; Zhenlang Lin (Molecular Neurobiology, 2025)

A New Approach for Exploring Reperfusion Brain Damage in Hypoxic Ischemic Encephalopathy - Tianlei Zhang; Zhiwei Zhang; Jiayi Geng; Kexin Lin; Xinru Lin; Mengdie Jiao; Jianghu Zhu; Xiaoling Guo; Zhenlang Lin (Molecular Neurobiology, 2024)

Batokine in Central Nervous System Diseases - Ming Shen; Min Zhang; Niping Mao; Zhenlang Lin (Molecular Neurobiology, 2023)

3′UTRs Regulate Mouse Ntrk2 mRNA Distribution in Cortical Neurons - Shangqin Chen; Jinjin Zhu; Peijun Li; Zhaonan Xia; Mengjing Tu; Zhenlang Lin; Baoji Xu; Xiaoqin Fu (Journal of Molecular Neuroscience, 2020)
There are two major isoforms of NTRK2 (neurotrophic receptor tyrosine kinase 2, or TrkB), full-length isoform with tyrosine kinase (TK) domain intact (+) and spliced isoform without tyrosine kinase domain (TK(−)). Within each isoform, there exist subtypes with minor modifications of the protein sequences. In human, the NTRK2 mRNA transcripts encoding TK(+) have same 3′UTRs, while the transcripts encoding subtypes of NTRK2 TK(−) have two completely different 3′UTRs. In mouse, the mRNA transcripts encoding same NTRK2 protein sequence for either TK(+) or TK(−) have long or short 3′UTRs, respectively. The physiological functions of these different 3′UTRs are still unknown. Pilocarpine stimulation increased Ntrk2 mRNA levels in soma, while the increase in synaptosome was smaller. FISH results further showed that mouse Ntrk2 transcripts with different 3′UTRs were distributed differently in cultured cortical neurons. The transcripts with long 3′UTR were distributed more in apical dendrites compared with transcripts with short 3′UTR. Our results provide evidence of non-coding 3′UTR function in regulating mRNA distribution in neurons.